Enhancing Medical Managers' Performance in Community Health Center: The Role of Accountability and Feedback - Pratolo, Suryo; Utami, Tiyas Puji; Ha, Nguyen Tran Thai (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study aims to test and obtain empirical evidence of felt accountability formed from formal and informal feedback in improving the performance of medical managers in community health centers in Indonesia. Design/Methodology/Approach: This study uses a quantitative approach with survey data collected from community health centers in various provinces in Indonesia. The data collected by 460 medical managers as a sample was processed using the Structural Equation Modeling using Partial Least Squares (SEM-PLS) approach. Research findings: Formal and informal feedback positively affect felt accountability. Felt accountability has a positive effect on improving the performance of medical managers in community health centers. Statistically, formal feedback has a greater influence than informal feedback, underscoring the importance of evaluation and performance appraisal in improving felt accountability. Theoretical contribution/Originality: This study is the first to empirically test felt accountability as a construct jointly shaped by formal and informal feedback in the unique hybrid roles of medical managers in Indonesian community health centers. It extends role theory into the primary health care context, filling a gap in accountability research focusing mainly on non-health sectors. Practitioner/Policy Implication: These findings have implications for community health managers to strengthen formal feedback systems to foster a stronger perception of accountability and to design managerial role training interventions aligned with the hybrid roles characteristics in health centers.